Interkoneksi Bank Syariah dengan Lembaga Filantropi Islam - Syaifullah, Hamli; Muttaqien, Muhammad Khaerul; Nazhif Hasbillah, Mohammad Fikri (BISNIS, 2022)
This study contains the interconnection model of Islamic banking with Islamic philanthropic institutions. The approach used is a case study, which focuses on an interconnection case in Islamic banking institutions, especially BPRS (Bank Pembiayaan Rakyat Syariah). The focus of the questions in this study are: (1) What is the pattern of interconnection between Islamic banking and Islamic philanthropic institutions?; (2) What is the impact of the interconnection for the two institutions? In order to get maximum research results, the researchers tried to do a comparison between one BPRS and another, related to the interconnection that occurred, namely at BPRS HIK Insan Cita Artha Jaya Parung Bogor with BPRS HIK Ciledug Tangerang City. The data used in this study are in the form of documents, (1) website documents owned by the two BPRS; (2) Financial Report from OJK; and (3) Financial Reports on the Website of each BPRS. The data analysis technique uses the Miles & Huberman interactive model. Referring to the research questions posed by the researchers, the research answers were obtained, including: (1) The pattern of interconnection developed between the Islamic banking industry and Islamic philanthropic institutions is passive interconnection; (2) The pattern of interconnection is passive, having an insignificant (small) impact on the collection of philanthropic funds.